Does a dominant party democracy erode constitutional legitimacy? An analysis of the African national congress and the South African constitution - Petersen, Shawwaal (Department of Public Law, 2020)
It has been twenty-five years that the ANC has enjoyed political hegemony and an investigation is required into whether the legitimacy of constitutional supremacy remains intact as a state functioning under a dominant political party. There are certain pathologies which develop in a dominant political party state, pathologies which lead to autocratic rule and which has the potential to undermine the constitutional institutions such as that created by the South African Constitution. The first aspect considered is the weakened oversight role of Parliament over the executive because of the democratic centralism policies practiced by the ANC. Democratic centralism entails strict party discipline which means Parliament cannot fully exercise its role in holding the executive accountable as envisaged in the Constitution. Provisions of the Electoral Act and the Anti-defection clause in the Constitution further allows a concentration of power in the top hierarchy of the dominant political party, thus ensuring that political leaders have all the might to ensure that self-preservation is the order of the day. Parliament which is meant to represent the electorate can be considered as a mere formal or hypothetical construction as the decisions of the dominant political party affects parliamentary processes. The second constitutional implication is that courts become overburdened to make decisions on matters which are better suited to another branch of government. Whilst constitutional review is a function of a thriving and working democracy, the argument presented here is that the judiciary has come to make decisions of a highly political nature. The reason for this is first the failure of Parliament to correctly exercise its oversight role and secondly the abuse of power by high ranking politicians in the dominant political party. The unintended consequence of a dominant political party state is the expansion of the role of the courts as the courts perform the ultimate watchdog role due to the loss of accountability in a dominant party regime. Thus, trespassing onto the terrain of other branches of government and in doing so undermining the independence of the judiciary itself. The last aspect which impedes constitutional legitimacy is the large-scale ‘capture' of state institutions. This phenomenon is linked to the ANC practice of cadre deployment which is a means to safeguard policies and to ensure that promises to the electorate are carried out by party loyalists. This practice in a dominant-party political landscape has created a loophole whereby democratic values and constitutional safeguards are often compromised. Pliable cadres are deployed to key positions and reporting lines are blurred which in turn has facilitated certain corrupt tendencies, leading to the demise of accountability, transparency and the efficiency of government and state-owned enterprises. Through analyzing case law and party policies and considering the pathologies associated with dominant party rule which has developed under the ANC's governance, it is aimed to determine whether a dominant political party erodes constitutional legitimacy in South Africa.